Does the road to land degradation neutrality in India is paved with restoration science?. Issue 5 (29th November 2021) - Singh, Kripal; Tewari, Shri Krishna
Abstract : The land in India is under severe threat of degradation. According to the 2016 Atlas of Land Degradation and Desertification, 29.3% of the total geographical area of India has been degraded or converted to deserts. To maximize ecological and economical benefits through the restoration of degraded ecosystems, India became a party to Bonn Challenge and United Nations Decade on Ecosystem Restoration 2021–2030 and has pledged to restore 26 million hectares of degraded land by 2030 during conference of parties 14 of United Nations Convention to Combat Desertification at Delhi. In Paris Agreement 2015, India has also pledged to increase forest tree cover through reforestation and afforestation initiatives, bringing degraded ecosystems under restoration, and sequester additional 2.5–3 billion tonnes of CO2 by 2030. These positive commitments are encouraging, but developing effective strategies for implementation of ecological restoration on the ground we need to understand (1) distribution of differently degraded ecosystems; (2) the status of scientific thoughtfulness and practices of restoration; and (3) review of empirical studies those can scientifically guide to pave the road to land degradation neutrality in India. Therefore, this study briefs about the distribution of degraded ecosystems, development of the science of restoration ecology, and its understanding and provide a synthesis of appropriate case studies on different degraded ecosystems, including forests, mined areas, and degraded and/or abandoned lands.